An insight of family business competitive resources: The role of social capital resources in family business growth and survival - Syed Amjad Hussain; Jakaria Dasan (Faculty of Business, Economics and Accountancy, 2021)
This paper offers few focus points by sighting the resources reserves exclusively available for family businesses (FBs); namely, social capital resources which include family prominence, family enrichment, and family continuity using the lens of resource-based view theory (RBV). The aim is to look into the impact of these resources on business performance, which is exclusively available to family firms considering the role of innovativeness. It is observed that most of the family businesses are failing during the transitional phase from one generation to the next. Only 12% make it to that distance, and the numbers getting past four generations before dropping to as short as 3%. The literature review focused on the exclusive resources held by the family businesses. Some of these become the compulsory part of business resource reserves and therefore firms need to learn to live with them considering their economic and non-economic benefits. The literature gap in FBs and RBV pointed that not all the firm’s resources provide economic contribution even if they are part of business resource reserves. Family firms’ decision-makers must consider the economic contribution of a particular resource when acquiring or developing its resource reserves to survive and grow.